The Interpretation Of Chinese Novel "Heaven Official’s Blessings" into Tailor Garment - Hung, Maggy Carroline; Mawardi, Tatang Khalid (Practice of Fashion and Textile Education Journal, 2026)
This study aims to examine how a literary character can be systematically translated into tailored garment design through a practice-based research approach. The research focuses on the character Hua Cheng from the Chinese historical fantasy novel “Heaven Official’s Blessing” and explores how narrative elements such as devotion, sacrifice, protection, and power can be embedded into tailoring structure. A qualitative, practice-based design research method was employed, in which the act of designing functioned as both the research process and the research outcome. Data were generated through the development of a moodboard, an influence page, and two technical sheets representing a tailored jacket and tailored pants. Analysis was conducted using reflective and interpretive techniques, examining how narrative intentions were transformed into visual and structural design decisions. The results show that literary narratives can be effectively translated into tailored garments through design elements such as fitted silhouettes, exaggerated shoulder structures, hybrid collar construction, and recurring triangular cutting and pocket details that symbolize pain and repeated sacrifice. The study demonstrates that tailoring can function as a narrative medium and provides a clear method for translating literary characters into contemporary fashion design.